The Role of p53 and Hypoxia in Nucleotide Excision Repair - Dregoesc, Diana (My University, 2009)
The nucleotide excision repair (NER) pathway is essential for repair of UV-induced bulky DNA lesions. NER is divided into two subpathways: global genome repair (GGR) and transcription-coupled repair (TCR). UVC radiation has been shown to result in the formation of bulky DNA lesions, which are removed by NER. Previous published reports have shown a role for the p53 tumour suppressor protein in GGR and TCR, but the involvement of p53 in TCR has been controversial. In addition, it has also been suggested that hypoxia affects NER and expression of p53. In the present work, the role of p53, hypoxia and HIF-lα in NER was investigated. It was determined that p53 overexpression in primary human fibroblasts resulted in up-regulation of both the GGR and TCR subpathways of a UV -damaged reporter gene. Pre-treatment of cells with low UVC-fluence and p53 overexpression also induced an upregulation of GGR and TCR. These results are consistent with a p53-dependent upregulation of TCR and GGR of the UVC-damaged reporter gene, as well with a UV-inducible TCR and GGR that is dependent on p53 expression prior to UV treatment. Hypoxia coupled to low pH induced a transient up-regulation of p53 expression and NER in human primary normal fibroblasts and a concomitant decrease in UVC sensitivity. In contrast, in tumour cells hypoxia coupled to low pH resulted in a delayed, but not absent up-regulation of NER, which was p53-independent and did not result in a decrease in UVC sensitivity. We report here that it is the early transient p53-dependent up-regulation induced by hypoxia coupled to acidosis in human primary normal fibroblasts that may play a significant role in cellular UVC sensitivity. These data suggest a different cellular NER response to hypoxia compared to hypoxia coupled to low pH. The NER response to hypoxia and hypoxia coupled with acidosis was also different in primary cells when compared to tumour-derived cells. It was demonstrated that expression of dominant-negative HIF-lα in rat prostate tumour cells results in a reduction in host cell reactivation (HCR) of a UV-damaged reporter gene when compared to that in wild-type HIF-lα cells under normoxic conditions suggesting that basal HIF-lα expression may play an important role in NER. In addition we showed that hypoxia induced an up-regulation of NER in human primary normal fibroblasts that was delayed, but not absent in TCR-deficient CSB cells, suggesting a role for hypoxia in up-regulation of the GGR pathway of NER of a UVdamaged reporter gene. In contrast, HIF-lα-overexpression under conditions of hypoxia resulted in a down-regulation of NER in normal fibroblasts, which was delayed, but not absent in CSB fibroblasts. These results suggest that HIF-1α and CSB are involved in a hypoxia-induced NER response. This work provides further evidence that both GGR and TCR are p53-dependent. In addition, this study provides evidence that hypoxia and hypoxia coupled to acidosis can up-regulate NER in both primary and tumour cells, and that HIF-lα and the CSB protein play an important role in a hypoxia-induced NER response.
Keywords: nucleotide excision repair; global genome repair; transcription-coupled repair; HIF-1α; primary human fibroblast; UVC radiation sensitivity; p53 regulation; acidosis; rat prostate tumour cells